Improvement of Louvers and Openings of Factory Building to Remove Heat through Natural Wind - Petchdee, Pannatat; Chungloo, Sudaporn (Journal of Architectural/Planning Research and Studies (JARS), 2022)
Heat accumulated in the factory building not only causes heat stress in workers but also reducesproductivity. This research is aimed at improving the opening and the louvers in consistent with the natural windand heat sources in buildings to remove heat. The study includes the measurement of the factory surfacetemperatures, air temperature and machinery heat and inputting into the model in ANSYS FLUENT 13.0, acomputational fluid dynamic program. The simulated results show the flow patterns and temperature of the airin the building. Simulation results show that the opening positions, angle of louvers and roof form bring warmair out of the building in two parts: heat attached to roof and heat in the working area. In addition, propercombination of opening position, louvers and roof form helps prevent the hot air from the top and increasingthe rate of heat flow out of work. The results show that the improvement of louvers increases wall openingfrom 10% to 30% and can reduce the working temperature down close to the ambient air of 32.5°C. Installationof opening on the roof can reduce the roof temperature by 10-12°C, resulting in preventing of radiative heattransfer from roof to working area.